Exploring of the Potential of Parthenium Weed Ash as Substitute for Commercial Alkali for Preparation of Laundry Soap: As a Means to Control Invasion of Parthenium - Adane, Legesse; Gelaye, Tesfaye; Tesfaye, Tegene (Frontiers in Sustainability, 2021)
Parthenium (Parthenium hysterophorus) weed is a noxious plant which inhabits many parts of the world. It is responsible for rapid environmental pollution causing a reduction in crop productivity by infesting farm lands and grazing lands. It also causes severe human and animal health problems. The aim of this study was assessing the potential of parthenium weed ash as a substitute for commercial alkali for the preparation of soap. Alkali solution was prepared from partheniun weed ash. Tests on its alkalinity properties revealed that the lye can be used for soap making. Similarly, the tests on physicochemical properties of the collected used cooking oil samples were found to be 141.0 ± 0.4–153.8 ± 0.33 mg KOH/g, 11.28 ± 0.5–14.1 ± 0.5 mg KOH/g, and 0.16 ± 0.2–0.19 ± 0.25 milieq/g for saponification value, acid value, and peroxide value, respectively. The data indicated that both the prepared lye solution and the collected used cooking oils would be suitable for soap preparation. Moreover, analyses of the moisture content, total alkali content, total fatty matter, the pH value, and chloride content of the prepared soap materials were found to be in the ranges of 10.5 ± 0.01–13 ± 0.01, 0.39 ± 0.01–1.63 ± 0.05%, 64.5 ± 0.16–76.4 ± 0.15%, 10.5 ± 0.03–10.63 ± 0.04, and 0.39 ± 0.2–0.45 ± 0.39%, respectively. The finding of the present study, is that it is possible to conclude that the Parthenium weed ash (or lye solution from this ash) and leftovers of used cooking oils can be used as cost-effective substitutes for commercial alkali solution and palm oil, respectively, for laundry soap preparation of acceptable grades. The finding also suggests that preparation of lye solution from parthenium weed ash can be used as an option for controlling the pollution of this invasive weed.